Publication Theories of Regulation - Franco, Diana (Pontificia Universidad Javeriana, 2013)
This article examines the relationships between regulation and competition, and thus, between law and economy. As part of this debate, the notion of reflexive law is of particular importance. This idea, which is not found within Law and Economics, but which is derived from systems theory, denotes a new form of law that captures the concept that the role of law is to stimulate self-regulation within society rather than prescribing rigid solutions for it.This article shed lights on the need for a broader theoretical category capable of explaining both the law and the economy as well as the prospects for these orders to come into alignment with one another. The potential reconciliation, as this article suggests, lies in seeing both law and the market order as forms of information and knowledge transmission, with their own distinctive logic. These concepts, already to be found both within systems theory and the Austrian/neoinstitutional economics, must be further articulated so as to create a functional language through which both sets of theories, economic and legal, can converge.